Sharing airspace with Uncrewed Aerial Vehicles (UAVs): Views of the General Aviation (GA) community. (July 2022) - Grote, Matt; Pilko, Aliaksei; Scanlan, James; Cherrett, Tom; Dickinson, Janet; Smith, Angela; Oakey, Andrew; Marsden, Greg
Abstract: Operations of Uncrewed Aerial Vehicles (UAVs or drones) are expanding, leading to competition for airspace with other users such as the General Aviation (GA) community, i.e., sports and leisure airspace users, particularly in uncontrolled airspace. As a result, there is an increasingly urgent need for a shared airspace resolution, whereby drones become integrated harmoniously in unsegregated operations with crewed aircraft, providing equitable airspace access for all. The purpose of the study was to engage with the GA community and elicit concerns and issues regarding the shared airspace concept as an initial step in the co-development of the future form of airspace. The method used was an online, interactive workshop with participants (n ~ 80) recruited from the GA community in the United Kingdom (UK). Data captured (verbal and written) were analysed qualitatively using thematic analysis, producing findings that summarised the issues identified on a range of different topics, grouped together under three over-arching themes: (1) operational environment; (2) technical and regulatory environment; and (3) equity and wider society. Almost a quarter of participants' comments (27%) were related to the opinion that shared airspace would only be possible if aircraft were fitted with Detect-And-Avoid (DAA) systems for de-confliction, based on onboard Electronic Conspicuity (EC) devices. Findings suggested that airspace management policies that establish equitable regulatory and technology environments regarding shared airspace are needed, and that those policies should be inclusive, having as a key aim the involvement of the GA community (and all other stakeholders) in the development process. The study represents a first step in the involvement of the wider aviation community in the co-design of shared airspace to include drones. Graphical abstract: Image 1 Highlights: UAV operations are expanding, leading to competition with other airspace users. General Aviation (GA) is an extensive airspace user affected by UAV operations. A shared airspace solution is required to integrate UAVs with crewed aircraft. Opinions from the GA community on shared airspace were collected and analysed. Development of the future form of airspace should include GA community engagement.